Pengaruh Investasi dan Tenaga Kerja Terhadap Pertumbuhan Ekonomi di Provinsi Sumatera Barat - Adyatma Prasetya, Raka; Taufiqurrahman, Muhammad; Aulia Maharani, Sri; Tumpak Tua Sirait, Yosia; Romarina, Arina (Masyarakat Ekonomi Syariah Bogor, 2025)
Regional economic growth is an important indicator in assessing the success of a region’s development. West Sumatra Province has experienced fluctuations in economic growth over the past decade, with growth in 2024 reaching only 3.96 percent, influenced by the weakening of public purchasing power. This condition indicates the need to analyze the production factors that play a role in driving regional economic growth. This study aims to analyze the effect of investment and labor on economic growth in West Sumatra Province during the period 2015–2024. The research method used is a quantitative approach with a causal design. Secondary data were obtained from publications by the Central Bureau of Statistics (BPS) and analyzed using normality tests, multiple linear regression, and the coefficient of determination. The results show that investment and labor have a positive and significant effect on economic growth, both partially and simultaneously. The coefficient of determination (R²) value of 0.659 indicates that 65.9 percent of the variation in economic growth can be explained by the two variables, while the remaining 34.1 percent is influenced by other factors outside the model. These findings emphasize the importance of increasing investment and optimizing labor as key strategies to strengthen sustainable economic growth in West Sumatra.